Bardet-Biedl syndrome and subaortic membrane: co-occurrence of two rare conditions - Osman Ziya Arık; Kamuran Tekin; Caner Türkoğlu; Murat Çaylı (KARE Publishing, 2013)
Bardet-Biedl Syndrome (BBS) is a rare autosomal recessive disorder with multiple morphological abnormalities. Clinical diagnosis is based on the presence of central obesity, polydactyly, rod-cone dystrophy, varying degrees of learning disability, hypogonadism (in men) and renal abnormalities. Cardiac involvement is a rare condition. We present a 28-year-old male with complaints of progressive dyspnea and palpitation diagnosed as BBS and subaortic discrete membrane. Careful echocardiographic evaluation of patients with BBS, such as in this case report, may allow us to discover novel cardiac abnormalities in this patient population.